Mapping Word-of-Mouth Pathways: Tie Strength and Contextual Reference Considerations - Ruslaini, Ruslaini; Benardi, Benardi (Studia Ekonomika, 2024)
This qualitative study explores "Mapping Word-of-Mouth Pathways: Tie Strength and Contextual Reference Considerations" with the aim of understanding the dynamics of word-of-mouth (WOM) communication. The research model investigates the influence of tie strength and contextual references on the propagation of WOM messages. A purposive sampling technique was employed to select participants representing diverse social networks and contexts. Data analysis involved thematic analysis to identify patterns and themes in the qualitative data. The findings reveal that tie strength plays a significant role in shaping the direction and intensity of WOM exchanges, with strong ties facilitating more direct and impactful communication. Contextual references, including situational factors and target group characteristics, also influence WOM pathways, guiding the dissemination of messages. This study contributes to a deeper understanding of WOM dynamics and provides insights for marketers and communicators seeking to leverage WOM effectively.